Subarray adaptive array beamforming algorithm based on LCMV - Wei Wang; Wei Xing Sheng; Bo Yu Qi (2005 Asia-Pacific Microwave Conference Proceedings, 2005)
A subarray adaptive beamforming algorithm that is subarray linearly constrained minimum variance (SLCMV) based on linearly constrained minimum variance (LCMV) is proposed in this paper. The computational load of the proposed SLCMV beamforming method is quite less than that of LCMV while keep the same degrees of freedom for beamforming. Comparative study between SLCMV and SARLS (subarray asynchronous recursive least square) is accomplished. Simulation results prove that the proposed SLCMV method is correct and requires less computational load than that of SARLS method.